Evaluating permafrost definitions for global permafrost area estimates in CMIP6 climate models - Norman J Steinert; Matvey V Debolskiy; Eleanor J Burke; Félix García-Pereira; Hanna Lee (Environmental Research Letters, 2023)
Global permafrost regions are undergoing significant changes due to global warming, whose assessments often rely on permafrost extent estimates derived from climate model simulations. These assessments employ a range of definitions for the presence of permafrost, leading to inconsistencies in the calculation of permafrost area. Here, we present permafrost area calculations using 10 different definitions for detecting permafrost presence based on either ground thermodynamics, soil hydrology, or air–ground coupling from an ensemble of 32 Earth system models. We find that variations between permafrost-presence definitions result in substantial differences of up to 18 million km ^2 , where any given model could both over- or underestimate the present-day permafrost area. Ground-thermodynamic-based definitions are, on average, comparable with observations but are subject to a large inter-model spread. The associated uncertainty of permafrost area estimates is reduced in definitions based on ground–air coupling. However, their representation of permafrost area strongly depends on how each model represents the ground–air coupling processes. The definition-based spread in permafrost area can affect estimates of permafrost-related impacts and feedbacks, such as quantifying permafrost carbon changes. For instance, the definition spread in permafrost area estimates can lead to differences in simulated permafrost-area soil carbon changes of up to 28%. We therefore emphasize the importance of consistent and well-justified permafrost-presence definitions for robust projections and accurate assessments of permafrost from climate model outputs.